Pengembangan Modul Praktikum Berbasis Projek Pabrikasi Komposit Dengan Metode Hand Lay Up - Maulana Fikri; Yuyun Estriyanto; Danar Susilo Wijayanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2022)
The purpose of this study is to develop composite learning practicum module based on project based learning at hand lay-up fabrication materials. This study means to fulfill the needs of composite subject at Mechanical Engineering Education Department in Faculty of Teacher Training and Education Sebelas Maret University. The method used in this study is the development based on the ADDIE (Analysis-Design-Development-Implement-Evaluate) model. Students of Mechanical Engineering Education Department are subject of this study. Questionnaire technique is used for Data collection. This method and technique are carried out to assess the development of composite practicum module content in terms of material, pedagogic, and language. Quantitative analysis techniques was conducted based on the the answers to the questionnaires. This study have an outcome to make even better composite practicum module with enhanced material, pictures, and evaluation. The rating score obtained from subject is 47,61 with very good criteria. The conclusions of this study are: (1) the development of composite learning practicum module based on project based learning has been done with eligibility standard. Therefore, it suitable as a guidebook for doing a proper composite practicum at Mechanical Engineering Education Department. (2) the developed composite learning practicum module has been done through FGD with lectures, then it being implemented on composite practicum activities, and it was rated by subject with average score 47,61 out of 52 that shows very good criteria. This developed practicum module is expected as a guidebook to help students doing proper composite practicum from preparation, analysis, self manufacturing, and able to improve abilities and skills.